MENTAL ACCOUNTING: MEMAKNAI KEBAHAGIAAN DARI SISI LAIN GAYA HIDUP MAHASISWA KOS - Elsa Eldista; Agung Budi Sulistiyo; Nur Hisamuddin (Universitas Jember, 2019)
This study aims to understand and analyze in depth about the financial behavior of college students in terms of addressing mental accounting phenomena in daily life, as well as being framed with lifestyles that shape perceptions about the happiness of life subjectively. The research subjects in this study were college students in particular the Department of Accounting, University of Jember. Qualitative research with a phenomenological approach is used because researchers want to explore the phenomenon as a whole according to events in the field. Data analysis technique is done by collecting data from interviews, then calcifying based on themes and drawing conclusions. The results showed a mental accounting phenomenon in college students' daily lives related to financial decision making and the treatment of income sources. Besides that students have also applied mental accounting quite wisely, especially in terms of financial decision making. Keywords: college students, happiness, lifestyle, mental accounting